2019
DOI: 10.1161/jaha.119.012602
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Site Coronary Vein Sampling Study on Cardiac Troponin T Degradation in Non–ST‐Segment–Elevation Myocardial Infarction: Toward a More Specific Cardiac Troponin T Assay

Abstract: Background Cardiac troponin T ( cTnT ) is seen in many other conditions besides myocardial infarction, and recent studies demonstrated distinct forms of cTnT . At present, the in vivo formation of these different cTnT forms is incompletely understood. We therefore performed a study on the composition of cTnT during the course of myocardial infarction, including coronary venous system samplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 31 publications
3
16
0
1
Order By: Relevance
“…The composition of circulating cTnT after MI has been previously described [20][21][22][23][24], showing the presence of intact cTnT, either as part of the ternary cTn T-I-C complex or as a free form, and two fragments (29 kDa and 15-18 kDa, respectively) (Figure 1.2B). Also, it was observed that the cTnT conformation changed over time [20,23]. On the other hand, in patients with end-stage renal disease (ESRD) only the smaller fragments (15-18 kDa) were observed [25].…”
Section: Cardiac Troponinsmentioning
confidence: 56%
See 4 more Smart Citations
“…The composition of circulating cTnT after MI has been previously described [20][21][22][23][24], showing the presence of intact cTnT, either as part of the ternary cTn T-I-C complex or as a free form, and two fragments (29 kDa and 15-18 kDa, respectively) (Figure 1.2B). Also, it was observed that the cTnT conformation changed over time [20,23]. On the other hand, in patients with end-stage renal disease (ESRD) only the smaller fragments (15-18 kDa) were observed [25].…”
Section: Cardiac Troponinsmentioning
confidence: 56%
“…NSTEMI patients as part of the TRAMICI study (n=71, Transcardiac Assessment of Myocardial Injury and Coronary Inflammation) were selected for the present study based on previously described criteria [23,243]. For an in-depth analysis, two patients with a culprit lesion in the left anterior descending coronary artery were selected: one with the shortest time interval between symptom onset and study procedure (patient 1); and another with the longest time interval (patients 2).…”
Section: Study Populationsmentioning
confidence: 99%
See 3 more Smart Citations